The biological age of 14-year-old boys and success in adult soccer: Do early maturers predominate in the top-level game? - Ostojic, S. M.; Castagna, C.; Calleja-Gonzalez, J.; Jukic, I.; Idrizovic, K.; Stojanovic, M. (Research in Sports Medicine, 2014)
Talent identification and development in soccer is often biased by maturation-related differences of young athletes. However, there is no information available about success rates for youth maturing at different tempos to achieve success in elite adult soccer. The purposes of this study were to determine the prevalence of different maturational groups among boys playing soccer, and to track them for competence in adult performance. A prospective cohort study design was used to follow 55, 14-year-old boys playing in Serbian youth soccer Division I over eight years. At the age of 14, biological age using skeletal age rates was determined, and participants were categorized as early maturers (EaM), normal maturers (NoM), and late maturers (LaM). Game competence for adult soccer at age 22 was described as elite if an individual played for clubs competing in top-five international soccer leagues (La Liga, Premier League, Bundesliga, Serie A, and Ligue 1), and/or has become a member of an adult National team. Among boys in our study group, 43.8% were categorized as EaM, 35.4% as NoM, and 20.8% as LaM (P = 0.11). A significant difference in biological age was found among maturational groups at age 14, with EaM > NoM > LaM (P > 0.0001). When assessed for adult soccer competence, 33.3% of participants (16 out of 48 players) succeed in achieving elite level. Elite soccer competence acquired 60.1% players from the group of LaM, 38.1% from NoM, and 11.8% from EaM (P > 0.0001). Our comparative analysis suggests that soccer excludes early maturing boys and favors late maturing boys as level of performance increases.